Automatic Language Identification of Spoken Hindi and Manipuri (International Journal of Innovative Research in Engineering & Management, 2021)
The technique of mapping continuous speech to the language  it belongs to is known as spoken language identification.  Front-ends for bilingual voice recognition frameworks, online  data retrieval, and automated customer handling in customer  support are all examples of spoken language identification  applications. The creation of a spoken language recognition  system for under-resourced languages of India such as Hindi  and Manipuri is presented in this research work. The  technology that has been developed is capable of accurately  identifying languages. This technology will be used to  demonstrate that it is capable of producing superior outcomes.  Experimental test runs and evaluation are used to determine if  the system is suitable for use in real-time identification  scenarios.
Keywords: Automatic Language Identification; Feature Extraction; PPRLM; Spoken Language Recognition